2022
DOI: 10.3310/chdc1642
|View full text |Cite
|
Sign up to set email alerts
|

Intensive support teams for adults with intellectual disabilities displaying challenging behaviour: the IST-ID mixed-methods study

Abstract: Background National policy recommends intensive support teams for all areas of England for adults with intellectual disabilities who display challenging behaviour. However, to the best of our knowledge, there has not been a systematic evaluation of intensive support teams to date. Objectives Our objectives were to identify and describe the geographical distribution and characteristics of intensive support teams in England; to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…ISTs are often poorly understood and defined (Hassiotis et al , 2020). Hassiotis et al (2020) identified two main models of IST, enhanced and independent, but they did not find a difference in outcome between the models (Hassiotis et al , 2022). This study contributes to an understanding of the role of ISTs by describing the processes and interventions of one team.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…ISTs are often poorly understood and defined (Hassiotis et al , 2020). Hassiotis et al (2020) identified two main models of IST, enhanced and independent, but they did not find a difference in outcome between the models (Hassiotis et al , 2022). This study contributes to an understanding of the role of ISTs by describing the processes and interventions of one team.…”
Section: Discussionmentioning
confidence: 95%
“…Essentially, one factor would answer "why" one variable affects the other, and this mechanism could produce a mediating effect. Hassiotis et al (2022) have compared enhanced and independent ISTs, but the specific impact of professional composition on outcomes for service-users has not been evaluated. Some ISTs are comprised entirely of psychologists and assistant psychologists, whereas others include psychologically trained members as part of the multidisciplinary team.…”
Section: Future Recommendationsmentioning
confidence: 99%
“…This is the first study in our knowledge to explore the views and experiences of multiple stakeholders of IST care in England. This qualitative study is part of a wider research programme that provided an overview of the current operation of ISTs and evaluated the clinical and cost effectiveness of two IST models in England (Hassiotis et al, 2021, 2022). Findings suggest that ISTs are often well received by family and paid carers and adults with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…This study is focused on ISTs that operate principally to address behaviour that challenges rather than mental ill health in adults with intellectual disabilities. It is part of a multicentre evaluation study of the two models of IST care operating in England (Hassiotis et al, 2021(Hassiotis et al, , 2022.…”
Section: Enhanced Provision Independent Provisionmentioning
confidence: 99%
“…For decades, reports have recommended the use of intensive support teams to manage behavioural crises in the community, prevent inappropriate admissions to mental health hospitals and facilitate discharge (Mansell, 2007; NHS England, 2015c). There are increasing numbers of intensive support teams in the United Kingdom, and they liaise with other services such as mental health teams, forensic community services, social care and commissioning teams (Hassiotis et al, 2022). Community forensic support teams were also recommended to support people who are at risk of coming into contact with the criminal justice system (NHS England, 2015c).…”
Section: Introductionmentioning
confidence: 99%